2019
DOI: 10.1101/795310
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Future of OA: A large-scale analysis projecting Open Access publication and readership

Abstract: Understanding the growth of open access (OA) is important for deciding funder policy, subscription allocation, and infrastructure planning.This study analyses the number of papers available as OA over time. The models includes both OA embargo data and the relative growth rates of different OA types over time, based on the OA status of 70 million journal articles published between 1950 and 2019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 6 publications
5
54
0
9
Order By: Relevance
“…Fukuzawa (2017) asserts that the share of OA journals more than doubled between 2004 and 2012 moving from about 7-15% of all journals. This steady progress in OA has been corroborated by a recent groundbreaking preprint of Piwowar et al (2019). Based on their findings that about a third of all articles are OA and that these OA articles received more than half of all article views in 2019, they predict a sustained decline of the closed access model with 44% of all articles being available as OA and their share in article views rising to 70% by 2025.…”
Section: Share Of Oa Journalsmentioning
confidence: 89%
“…Fukuzawa (2017) asserts that the share of OA journals more than doubled between 2004 and 2012 moving from about 7-15% of all journals. This steady progress in OA has been corroborated by a recent groundbreaking preprint of Piwowar et al (2019). Based on their findings that about a third of all articles are OA and that these OA articles received more than half of all article views in 2019, they predict a sustained decline of the closed access model with 44% of all articles being available as OA and their share in article views rising to 70% by 2025.…”
Section: Share Of Oa Journalsmentioning
confidence: 89%
“…Heather Piwowar and her colleagues estimate that in 2019 31% of all journal articles were open access and these articles accounted for 52% of article views. By 2025, they project 44% of all articles will be open access, and 70% of article views are be to these open assess articles (Piwowar, et al, 2018 andOrr, 2019). So, a full open access publishing system does not seem beyond the realm of possibility.…”
Section: Question 2: What New Business Models and Practices For Scholmentioning
confidence: 99%
“…Piwowar et al (2018) showed that the global proportion of open access articles was about 45% for those published in 2015, compared to around 5% before 1990. A more recent projection suggests that 44% of all outputs ever published will be freely accessible in 2025 (Piwowar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%